(untitled) (Fiep Bulletin - online, 2014)
Discussions on a posture that includes educational playfulness accentuated in the current school context , increasing the chances that students learn through meaningful practice , contextualized and dynamic . In this article: " The importance of knowing playfulness in academic research concepts , fundamentals and practices of playfulness , using it as a vehicle to work essential expressivity , affective , and psychomotor skills and sociability , in order to facilitate the development process teaching and learning of children and their full cognitive, physical, emotional and social , ie the integral development . To achieve this goal , education " playful " demand and help form the personality of the individual , developing your creativity , allowing you to earn your identity and your balance . The play activity , so it is of paramount importance , especially the physical education teacher who needs to contextualize these concepts in teaching . For this research, the method used was the literature , by renowned authors and the laws governing physical education . It is intended to prove that playfulness can not be regarded as secondary , should especially get place in school, so that students feel the pleasure of discovery and become active participants and involved in the teaching-learning process .